Associations between white matter micro- and macrostructural integrity, neurophysiology, and motor function in people with multiple sclerosis - Patrick, Christopher Michael, author; Fling, Brett W., advisor; Clapp, Tod R., committee member; LaRocca, Thomas J., committee member; Tracy, Brian L., committee member (Colorado State University. Libraries, 2025)
Movement is one of the most fundamental expressions of brain function. From "simple" movements like reaching and walking to the most complex aerial gymnastic stunts, voluntary movement emerges from the seamless integration of sensory input, motor planning, and execution. Such integration relies on a symphony of widespread, dynamic communication across cortical, subcortical, brainstem, and spinal regions orchestrated to produce smooth, purposeful movement. In this way, the brain does not merely support movement, it is shaped by and for it. However, when the integrity of these neural systems is disrupted, as in neurodegenerative conditions like multiple sclerosis (MS), the consequences can be life altering, leading to impaired mobility, loss of independence, and diminished quality of life. MS is a chronic disease of the central nervous system (CNS) that results in neural injury, impairing communication within neural networks. Damage to neurons and their connections gives rise to a range of heterogeneous symptoms, among which challenges with balance and mobility are among the most common and impactful. Understanding how MS-related damage to the CNS contributes to functional impairment requires tools that can capture different aspects of neural integrity and motor performance. This dissertation integrates biomechanical, neurophysiological, and neuroimaging approaches to characterize the state of the CNS in people with MS and to link these metrics to real-world movement abilities. Using biomechanical techniques, the first study found that individuals with MS control their bodyweight differently during a sit-to-stand transfer movement, producing less force and power than neurotypical controls, with power helping to distinguish fallers from non-fallers. Building on this, the second study examined corticospinal integrity using neurophysiological measures, finding that altered excitability and prolonged conduction were associated with reduced force during both isolated muscle contractions and a sit-to-stand transfer movement, linking corticospinal function to movement performance. The third study used advanced neuroimaging techniques, including diffusion tensor imaging, diffusion kurtosis imaging, and fixel-based analysis, to assess corticospinal tract integrity in people with MS, revealing white matter alterations throughout the corticospinal tract. Among these methods, fixel-based metrics demonstrated the strongest associations with clinical measures of balance, disability, and neurophysiological outcomes. Finally, recognizing that the corticospinal tract is not the sole motor pathway, the fourth study examined the corticoreticulospinal tract and found that fiber density in this pathway correlates with balance and walking performance in people with MS. Together, these studies illustrate the complex ways in which neural damage in MS disrupts the intricate networks essential for effective movement. By employing a multimodal approach, this work enhances understanding of how structural and functional changes across multiple motor pathways contribute to motor function. These insights may help inform future efforts to assess and manage mobility impairments in people with MS.
Keywords: diffusion magnetic resonance imaging; neuromechanics; clinical assessments; transcranial magnetic stimulation; multiple sclerosis